A Manualized Behavioral Therapy Intervention for Youth with Autism Spectrum Disorder and Substance Use Disorder - McKowen, James; Berger, Amy; Towbin, Joshua; Yule, Amy M.; Woodward, Diana; Nowinski, Lisa; Forchelli, Gina; Meyers, Robert J.; Joshi, Gagan; Wilens, Timothy E. (Case Reports in Psychiatry, 2023)
Research highlights the increasing overlap of autism spectrum disorder and substance use disorders in young people. However, no behavioral treatments exist addressing this comorbidity despite great need. A team of clinicians developed an integrated behavioral protocol addressing substance use in youth with autism spectrum disorder. The multidisciplinary team developed 12 youth, 7 parent, and 3 joint modules based on established evidence-based therapies shown to have effectiveness separately addressing autism spectrum and substance use. Two cases are discussed to illuminate this integrated intervention. Adaptations to the protocol were made during feedback from patients and their parents. Further research is needed to determine the effectiveness of this preliminary protocol.